PEMANFAATAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus.) SEBAGAI BAHAN TAMBAHAN DALAM PEMBUATAN ES KRIM - Johan, Vonny Setiaries; Hamzah, Faizah; ', Waladi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study was red dragon fruit peel can be used as natural dyes. The purpose of to get the best formulations of red dragon fruit peel ice cream by physical properties, fiber and organoleptic test. This research used a completely randomized design (CRD) with four treatments and four replications. The treatment in this study are E0 (without the addition peel of red dragon fruit), E1 (addition of 2% red dragon fruit peel), E2 (addition of 4% red dragon fruit peel), and E3 (addition of 6% red dragon fruit peel). Data obtained were treated by analysis of variance followed by Duncan New Multiple Range Test (DNMRT) the level of 5%. The results showed that the addition of red dragon fruit peel had significant effect on the overrun, ice cream melting time, fiber content, hedonic of texture, colour, overall acceptance and descriptive of texture, color and flavor. The addition of red dragon fruit peel had not significant effect on hedonic of taste, flavor and descriptive sensory. The best formulation this study is addition of 6% red dragon fruit peel. Keywords : Red dragon fruit peel, natural dyes, ice cream.